Fiasko reformy polityki imigracyjnej, kontroli granic zewnętrznych oraz polityki azylowej Unii Europejskiej w latach 2015-2020: Analiza krytyczna (Politeja, 2023)
THE FAILURE OF THE REFORM OF THE EUROPEAN UNION’S IMMIGRATION POLICY, EXTERNAL BORDER CONTROL, AND ASYLUM POLICY BETWEEN 2015 AND 2020: A CRITICAL ANALYSISThe primary research objective of the article is to evaluate the reform of the immigration, external border control and asylum policy of the European Union between 2015 and 2020. The author formulates two research hypotheses. The first is based on the assumption that the legislative packages presented by the European Commission in 2015-2016 and then in 2018 have almost completely failed. The second hypothesis is that the idea of establishing a permanent resettlement mechanism as a means to overcome the migration crisis in the Union in 2015-2016 and address the future migration challenges  of the EU has generally failed. Instead, the EU’s temporary resettlement mechanisms in place between 2015 and 2017 and the 1:1 resettlement mechanism between the EU and Turkey introduced in 2016 have worked well. The author then formulates two research questions: firstly, why have the legislative acts of the European Commission largely failed?; and secondly, why has the temporary relocation of asylum seekers in the EU generally been successful?